PENGARUH PENGGUNAAN E-LKPD BERBASIS PROBLEM BASED LEARNING TERHADAP PEMAHAMAN KONSEP PADA MATERI SISTEM PENCERNAAN MANUSIA - Azizah Meilina Dhiah Evanti; Lilik Mawartiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was aimed to know the effect of using E-LKPD based on Problem Based Learning on conceptual understanding of the human digestive system material. Conceptual understanding is included in the dimensions of cognitive processes. This study was conducted at SMP Negeri 2 Tuban. The research methodused was a quasi- experimental design with a pretest-posttest control group design. Sampling was carried out using a purposive sampling technique. The sample in this study were students of class VIII.G as a control class with conventional learning and VIII.H as an experimental class with learning using E-LKPD based on Problem Based Learning. The sample in each group was 31 people for the control class and 32 people for the experimental class. Data collection was carried out using E-LKPD which contained questions in accordance with the PBL syntax in students' conceptual understanding of the human digestive system material. Data analysis using the polled variance t-test obtained the results of t count = 9.25 greater than t table = 1.99. Thismeans that t count > t table, and a significant value of 0.05 or 5%. So Ho is rejected and Ha is accepted at a significant level of 5% so it is concluded that there is a significant difference between the average pre-test and post-test scores of the experimental group and the control group. This shows that there is an influence of the use of E-LKPD based on Problem Based Learning on conceptual understanding of the human digestive system material.